Sedimentology and depositional environment of the Lower Devonian Wapske Formation, Perth-Andover/Mount Carleton region, northwestern New Brunswick - Han, Yaojun; Pickerill, Ron (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1995)
The Lower Devonian Wapske Formation of the Tobique Group in the Perth-Andover/Mount Carleton region, northwestern New Brunswick, forms part of the tectonostratigraphic Tobique Zone. In this area, the formation, 4000 to 9000 m thick, is interpreted to comprise seven regionally recognizable sedimentary facies. These are: conglomerate facies (Facies 1), massive and parallel-laminated sandstone facies (Facies 2), thin- to thick-bedded sandstone with minor mudstone interbeds and/or mud-capped facies (Facies 3), thin-bedded sandstone and mud-stone facies (Facies 4), thin-bedded, graded, fine-grained sandstone facies (Facies 5), very thin-bedded, finegrained sandstone and silty mudstone facies (Facies 6), and thin- and medium-bedded siltstone and mudstone facies (Facies 7). The absence of unequivocal shallow-water sedimentary structures, depositional cycles and in situ body fossils in these lithofacies and, instead, the presence of Bouma depositional sequences and deep-water trace-fossil associations, is supportive of a deep-marine origin (below storm-wave base) for the Wapske Formation in the study area. Accordingly, the facies are grouped into five facies associations interpreted to reflect a deep-marine fan system comprising distributary channels, depositional lobes, lobe or fan fringes, and interchannel areas associated with a basin plain. Regional considerations suggest that the Wapske Formation records a transition from shallow-water marine, locally terrestrial, deposition to the east and southeast of the study area, to deep-water deposits, as described herein, to the west and northwest in the Perth-Andover/Mount Carleton region.